HUBUNGAN LATIHAN SENAM HAMIL DAN PARITAS DENGAN LAMA WAKTU PERSALINAN KALA I FASE AKTIF PADA IBU BERSALIN DI TPMB. NENENG HALIMATUL SA’DIAH CIKARANG SELATAN TAHUN 2025 - Yuli Erlina,; Ermaya Sari Bayu Ningsih, (Journal of Innovation Research and Knowledge, 2025)
Prolonged labor is the final stage of a labor that is obstructed and lasts too long, a condition that is common in primiparous pregnant women. The WHO estimates that prolonged labor currently occurs in 17% of all deliveries worldwide. The Indonesian Demographic and Health Survey (IDHS) reports that prolonged labor is the majority of childbirth complications (30%). To facilitate normal labor, prenatal exercise is performed to reduce the incidence of prolonged labor. The purpose of this study was to determine the relationship between prenatal exercise and parity with the duration of the active phase of the first stage of labor among women giving birth at the Neneng Halimatul Sa'diah TPMB, South Cikarang, in 2025.This study was quantitative analytical, using a cross-sectional study design. The sample consisted of 80 women giving birth at the Neneng Halimatul Sa'diah TPMB, South Cikarang, between January and June 2025. The instruments used in this study were primary and secondary data. Data were analyzed using the chi-square test. The results showed that the variables associated with the duration of the first stage of labor during the active phase in women giving birth at the TPMB Neneng Halimatul Sa'diah, South Cikarang were pregnancy exercise (P-value = 0.002) with an OR of 80.00 (95% CI 21.40-467.3) and parity (P-value = 0.039) with an OR of 0.255 (95% CI 0.077-0.847).Conclusion: There is a significant relationship between pregnancy exercise and parity variables with the duration of the first stage of labor during the active phase in women giving birth at the TPMB Neneng Halimatul Sa'diah, South Cikarang. Pregnant women are expected to maintain their pregnancies and are encouraged to participate in pregnancy exercise programs so that the delivery process proceeds normally. TPMB Neneng Halimatul Sa'diah